UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL DAUN KEREHAU (Callicarpa longifolia Lam) TERHADAP Escherichia coli dan Staphylococcus aureus - Eko Kusumawati; Anita Apriliana; Khusnul Khatimah (Jurnal Ilmiah Manuntung, 2016)
Kerehau (Callicarpa longifolia Lam) is a plant that has traditionally efficacious as a cure colds and diarrhea. Part used as medicine are the leaves. This study aims to determine the antibacterial activity of ethanol extract of leaves kerehau on Escherichia coli and Staphylococcus aureus. Kerehau leaf extract prepared by maceration method using ethanol 70%, with a test concentration of 10%, 25%, 50%, and 100% and chloramphenicol 0.1% (w / v) as a positive control and dimethyl sulfoxide 1% (v / v) as a negative control. The results of antibacterial activity test with extract concentrations of 25%, 50% and 100% in Escherichia coli is 9.45 mm, 12.21 mm and 17.38 mm, for the positive control is 21.85 mm. The results of antibacterial activity test with extract concentrations of 10%, 25%, 50% and 100% in Staphylococcus aureus was 7.3 mm, 9.85 mm, 13.65 mm and 20.58 mm, for the positive control was 24.05 mm. The antibacterial activity was analyzed by One Way ANOVA showed significant differences between treatments